PERLINDUNGAN HUKUM DATA PRIBADI DI INDONESIA - Siti Yuniarti (Bina Nusantara University, 2019)
Attention to the protection of personal data increases with the development of technology, information and communication (ICT). Collecting, managing and storing personal data is increasingly easy to do by using the technology. These conditions are vulnerable to individual privacy. Privacy is recognized as a human right that required s a legal protection of personal data. As a legal state, Indonesia provides legal protection of human rights as stated firmly on UUD 1945. On the other hand, Indonesia is open to utilization of information and communication technology, including the internet. As consequences, Indonesia has to ensure that data protection has been covered by law. Therefore, using a normative juridical research method, this paper seeks to describe legal protection for personal data in Indonesia today. It shows that legal protection of personal data only accommodated on sectoral regulation that acquired a specific comprehensive act.